Mixed convection due to a rotating cylinder in a 3D corrugated cavity filled with single walled CNT-water nanofluid - Selimefendigil, Fatih; Öztop, Hakan Fehmi; Abu-Hamdeh, Nidal H. (Springer, 2019)
Analysis of mixed convection due to a rotating inner cylinder in a corrugated three-dimensional cavity filled with carbon nanotube-water nanofluid was performed. Numerical simulations were performed by using Galerkin weighted residual finite element method. The three-dimensional corrugated cavity was differentially heated form the vertical surfaces, and an inner rotating adiabatic cylinder was used. Influence of Rayleigh number (between 10(4) and 10(6)), angular rotational velocity of the cylinder (between - 50 and 50 rad/s), height (between H / 10 and H / 3) and number of triangular waves (between 1 and 16) and solid nanoparticle volume fraction (between 0 and 0.04) on the convective heat transfer characteristics was analyzed. It was observed that average heat transfer augments significantly by changing the nanoparticle volume fraction and up to 128% of enhancement is obtained. Depending on the rotational direction of the cylinder, average Nusselt number enhances 68% in the three-dimensional cavity. Surface corrugation parameters are not as effective as solid particle volume fraction and angular rotational speed of the cylinder on the heat transfer enhancements. Finally, a correlation for the average Nusselt number along the cold surface was provided which is dependent upon the angular rotational speed of the cylinder and Rayleigh number.
Keywords: Three-dimensional cavity; Corrugated wall; Nanofluid and FEM; Rotating cylinder